A Gendered Analysis of Fisherfolk's Livelihood Adaptation and Coping Responses in the Face of a Seasonal Fishing Ban in Tamil Nadu & Puducherry, India. (October 2017) - Novak Colwell, Julia M.; Axelrod, Mark; Salim, Shyam S.; Velvizhi, S.
Highlights: Intersectionality framework was applied to understand responses to a fishing ban. Locally relevant measures of power, class, and sex are operationalized. Women were more likely than men to employ reactive coping strategies. However, an individual's power and class changes this relationship. Power and class have different effects on men's and women's stress responses. Summary: This study investigates how people respond to economic stresses incurred as a result of natural resource regulations. Previous research has demonstrated that in some cases, men and women adapt differently to livelihood stresses. We argue that looking only at an individual's sex is insufficient for understanding why they adapt the way they do. Instead, using the framework of intersectionality, we examine individuals' adaptation strategies and coping responses influenced not only by their sex but also their power and class. Using the case of a closed fishing season in Tamil Nadu and Puducherry, India we employ interviews, seasonal activities calendars, and surveys to identify key variables that influence an individual's likelihood of employing reactive strategies that may threaten their longer term livelihood sustainability. We show that if we categorize individuals only by sex, then women are more likely to resort to reactive coping than men. However, this sex divide in reactive coping is driven by particular subsets of people who also lack power and/or capital. Furthermore, we find that power and class lead to different outcomes for men and women, with networked power most helpful to women above a certain financial threshold. This study highlights the necessity of examining gender and livelihood adaptations beyond the male versus female dichotomy: considering intersecting and locally relevant measures of power, class, and sex are pivotal in understanding why people adapt and cope the way they do. This understanding of adaptation options may also have implications for resource management decisions that do not force individuals to choose between long-term livelihood resilience and response to immediate stresses.